Mitochondrial dysfunction as a central hub linking Na+/Ca2+ homeostasis and inflammation in ischemic arrhythmias: therapeutic implications - Sun, Siyu; Zhang, Zhanrui; Li, Yuxi; Zhang, Hui; Guo, Huige; Chen, Guohui; Wei, Pei; Lin, Fei; Zhao, Guoan (Frontiers in Cardiovascular Medicine, 2025)
Ventricular arrhythmia is the primary cause of sudden cardiac death in patients with myocardial infarction (MI). Myocardial inflammation and Na+/Ca2+ imbalance are the main triggering factors for life-threatening tachyarrhythmias after MI, which induce ion channel dysfunction, intracellular environment imbalance, tissue damage, and other alterations, subsequently resulting in modifications in cardiac conduction velocity and pathways. Subsequent adverse fibrotic remodeling provides a substrate for ventricular tachyarrhythmia (VT). Mitochondria, as the intersection site of these pathophysiological changes and the center of Na+/Ca2+ homeostasis and inflammatory crosstalk, may be key sites for the occurrence and development of ischemic arrhythmia. This review briefly outlines the roles of inflammation, Na+/Ca2+ homeostasis, and mitochondria in the damage, repair, and structural remodeling of infarcted hearts, in which these three are interconnected to provide a large number of substrates for VT.